Grundtvig og den ældre danske salmedigtning - Sørensen, Jørgen (Grundtvig-studier, 1964)
Grundtvig and The Old Danish Hymns.By Jørgen Sørensen.Translated by W. Glyn Jones, Ph. D. In 1806 Gr. took part in a discussion regarding a revision of the liturgy. He was at the time a recent convert to Romanticism, and in his contribution he also expresses his views on hymns, maintaining that poetry is of primary importance for the meeting with “the eternal”. Even at this early date Gr. Is ritical of the Evangelical-Christian Hymnal (Evangelisk-Kristelig Psalmebog —abbreviated ECH), which “could have borrowed more from the older one”.In the introduction to “ Fair are the heavens blue” (Deilig er den Himmel blaa” in “ The Soothsayer” (Sandsigeren) 1811, Gr. again deals with the older hymns. The article was written after the crisis of December 1810 and is characterised by Gr.s newly-acquired aggressiveness towards rationalism, which was occasioned by the orthodox Bible faith he now professed. The weight of his attack is directed towards ECH, or, more precisely, towards its lack of historical hymns. This attack is supported by historical, aesthetic and theological arguments, and though it was the last of these which Gr. considered most important, it is the first which is of most interest in the present context. For it evolves that Gr.’s knowledge of older Danish hymns was quite limited at this period, and his arguments are based merely on his knowledge of “ The Winter Part” (Vinterparten), the hymn-book by Kingo which failed to be recognised as the authorised hymn-book in 1689. This assertion is supported by an examination of the prototypes Gr. used for the adaptations of Danish hymns which he did in 1810- 1 1.The aesthetic attack in 1811 is a continuation of that from 1807, but more fully elaborated. The historical hymns, Gr. maintains, are of greater value than the rest because they are aesthetically more satisfying. It is interesting to note that the great significance which Romanticism taught Gr. to attribute to poetry survived the crisis of 1810- 1 1 .Finally, with regard to the theological attack, Gr. comes by means of random argumentation to the conclusion that the lack of historical hymns is synonymous with a lack of true Christianity.In his history of the world from 1812 Gr. also deals with hymns, and a summary of his thought shows that on the basis of older hymn-writing he makes three demands on a hymn: it must be Christian, i. e. biblical in content and language, it must be poetical without being grandiloquent, because at the same time it must be such as will be understood by the people (folkelig). Gr. Finds the hymn-books from the Reformation sufficient for their day because of the ardent devotional outlook of the age, despite the fact that the hymns “were not strikingly poetical”. Kingo’s hymn-book excelled on account of its union of true Christianity and poetry, while Høeg Guldberg’s was not aimed at the ordinary people and therefore was a mistake. Finally ECH was a complete failure, since it in no way corresponded to Gr.s conception of what hymns should be.It was natural, therefore, that Gr. should desire a new hymn-book, but at the same time he realised that this was not immediately possible. On the other hand he could quite well strike a blow for the old hymns by adapting them for private use in the family circle. This he announced as early as 1811, but the collection never appeared, presumably because Gr. did not find so many champions of orthodox Christianity as he had expected. And so only a few adaptations were made before 1832, when Gr.’s main work on the adaptation of hymns gathered momentum.In some critical comments on hymns by Ingemann and Kingo, which he wrote in 1825 and 1828, Gr. also deals with more general questions connected with the writing of hymns, and there is no apparent change in his views on this subject or in his attitude towards the older hymn-books, except in the case of ECH, which receives a share of praise for including hymns stressing people’s natural relationships to God, each other and temporal things.In discussing the need for a replacement for ECH Gr. also shows a distinct change of view, as he now wants one or more new hymn-books in which the old hymns, suitably adapted, should be included. Gr. had always felt the desire to resuscitate these old hymns, but the problem had been whether, and to what extent, they should be altered.In 1832 Gr. is uncertain, but in 1837 the problem has been solved: as “a poet and a reader of good taste” he must desire to see them reprinted in their original form, but as the “servant of a congregation” he must seek to reintroduce the old hymns, even if this meant adapting them. In 1837 and subsequently Gr. felt himself entirely as the servant of a congregation, while in 1832 he still wavered in this attitude. Gr.s conception of his own abilities in this field is closely related to this. Both in 1828 and 1832 he appears sceptical, but this feeling also disappears in the following years.Finally, a development takes place during these years in the scope of the alterations Gr. made to each individual hymn. A comparison of those included in Hagen’s collection in 1832 with the form the same hymns were given in the Song Collection (Sangværk) of 1837 will show that in the latter Gr. treats his prototype much more freely. The question then is, what can have caused this development in these three spheres, intimately connected with each other as they naturally are. In a polemic in connection with the publication of the model for a new hymnbook in 1845 Gr. writes that he agrees that not only hymns like his own and Kingo’s should be included, but that other tones should also be heard. It is the personalities of the individual hymn-writers which must be removed; in other words he means more or less that characteristic theological views must give way to that which is of the Church (det kirkelige), or, as he specifically says elsewhere: “let the individual characteristics be subordinated to that which is of the Church and the people”. Gr. saw his own views on the Church not as being equal to other theological conceptions, but as being in a completely different category which encompassed all the others.Thus he can talk of removing the personality of other poets, and even of removing his own, and replacing them with that which is of the Church, but in nyone else’s eyes this is precisely what is specifically Grundtvigian. The consequences which this view of the Church had for hymn-writing were not entirely obvious to Gr. in 1832 when he still viewed hymns as results of “personalities” and sought to make his own hymns harmonise with this. In 1836 he came to see the Danish hymns as part of a far greater unit, and so the dilemma of 1832 was solved. For the same reason Gr. could rely on his own abilities, for the hymns should no longer be expressions of personalities, but of the Church, and consequently they could and must be thoroughly revised. And for whom should it be more natural to do this than for the poet who made the incomparable discovery (den mageløse opdagelse)?